Influence of financial variables on the development of rural communes of Eastern Poland in 2009-2018 - Andrzej Pawlik; Paweł Dziekański; Jarosław W. Przybytniowski (Risks, 2021)
Communes are a place of both economic activity and creation development. They have autonomy in making decisions in the fields of financial, human, and material resources. This research was carried out with the use of a synthetic measure. The aim was to show the impact of financial variables on the development process of rural communes in eastern Poland. The data were collected in spatial terms for 484 rural communes from the region of eastern Poland. The choice of variables was conditioned by the availability of GUS data for the period 2009-2018. The distribution of the evaluation of the development and financial situation of rural communes in eastern Poland was spatially polarized. The reason for the low impact of financial conditions on the development of rural communes in eastern Poland is their dependence on income transferred from the state budget. This stiffens and at the same time stabilizes the financial economy, making it relatively insensitive to the influence of other factors. Low independence can be a significant barrier to future local development. Finance and the economy are intertwined. Actions taken with respect to these must be based on analyses that facilitate making the right decisions.
Keywords: 330; competitiveness; financial security; public sector; rural municipalities; synthetic measure; TOPSIS method